A THE IMPORTANCE OF FORMING INTERCULTURAL COMMUNICATION IN FOREIGN LANGUAGE TEACHING: THE IMPORTANCE OF FORMING INTERCULTURAL COMMUNICATION IN FOREIGN LANGUAGE TEACHING - Akhmedov, Akhmedov (Журнал иностранных языков и лингвистики, 2022)
Culture is a word for the ’way of life’ of groups of people, meaning the way they do things. Different groups may have different cultures. A culture is passed on to the next generation by learning, whereas genetics are passed on by heredity. Culture is seen in people’s writing, religion, music, clothes, cooking and in what they do.This article addresses issues such as language, culture, typology of cultures, types of communication, oral communication, cultural adaptation, intercultural barriers and conflicts. Linguoculturological issues related to the concept of language and culture, which are currently attracting the attention of everyone in linguistics, are being studied by most scholars – but have not been resolved. It is noteworthy that this article focuses on this issue – a new field of linguistics – intercultural relations in the process of teaching a foreign language.